Rangkai Nusantara Digital Innovation for Strengthening National Values and Pancasila-Based Character Education - Adha, Muhammad Mona; Perdana, Dayu Rika; Kusrini, Nani; Abung, Miranda (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
The decline of national values and the weakening of Pancasila-based character education among young generations pose a significant challenge in shaping Indonesia’s Golden Generation 2045. This community service program, entitled Rangkai Nusantara, aims to develop a digital innovation platform that strengthens national values and Pancasila-oriented character education. The program was implemented through participatory, technology-based training activities involving interactive workshops, digital content creation, mentoring, and dissemination of student-produced educational works. The target group consisted of junior high school students in Bandar Lampung. The results showed a significant improvement in students’ understanding of Pancasila values, creative digital literacy, and the establishment of a youth network promoting national values through digital platforms. This program demonstrates that integrating digital innovation into character education can foster patriotic awareness, digital citizenship, and moral integrity. Rangkai Nusantara thus serves as a replicable model of technology-based character education to empower Indonesia’s young generation in the digital era.